Friday

March 27, 2015

March 27, 2015

Posted by **Tony** on Sunday, December 17, 2006 at 8:35pm.

im getting rele confused on this. ok here is the prob.

x+y=5

x-2y=-4

Multiply equation 1 by -1.

Add equation 1 to equation 2. The x term cancels. Solve for y.

THEN, put the value of y into either equation and solve for x.

Finally, put the value of x and y into the OTHER equation and see if those values satisfy the equation.

- MATH -
**Anon**, Thursday, July 17, 2014 at 12:19pmMultiplying Equation 1 by -1 you get:

-x-y=-5

Adding that to equation 2 you get:

-x -y = -5

+ x -2y = -4

-------------------

-3y = -9

Divide both sides by -3 and you get

y=3

Put that back into either equation and you can solve for x

x+y=5

x+3=5

x+3-3=5-3

x=2

So x=2, y=3 should be the solutions.

Check this in the other equation, x-2y=-4

2-2(3) = -4

2-6 = -4 why yes it does! :-)

**Answer this Question**

**Related Questions**

maths algebra - HI STEVE, THANKS for your reply back it was the wrong answer ...

Math - Could someone please help me. Solve the linear equation by substitution. ...

math,correction please.. - (x)/(x-2) - (x+1)/(x) = (8)/(x^2-2x) I keep getting x...

math - I need help solve the equation by fractions 8/(21-y) = 12/(y+19) I think ...

chemistry...Please Help - I posted this below and received help but im still ...

Math - Can someone please help with this problem? Solve by the elimination ...

maths - im trying to rearrange the following equation for x but getting confused...

MATHS - i need a lil help with this If x=2 is a root of the equation 6x^3 - px^2...

maths - 1x+2y=5 3x+7y=18 x= y= Multiply equation 1 by -3, add to equation 2 (...

Algebra - Solve each literal equations for the indicated variable D = C - s/n ( ...